Erosion-reducing potential of Salix psammophila roots in the water–wind crisscrossed erosion region of the Chinese Loess Plateau: A simulated investigation - Zhang, Zheng; Yu, Weijie; Li, Qiang; Sun, Hui; Feng, Zhidao; Zou, Jiatong (Frontiers in Environmental Science, 2023)
Laboratory-simulated experiments under a one-way wind erosion–rain erosion sequence were conducted to investigate the effect of S. psammophila roots on wind and water erosion processes and quantify its erosion-reducing potential. With the collected soil of sandy loam and planted shrub of S. psammophila, 16 soil boxes including bare and root-permeated soils were arranged in March 2017 and conducted in August 2017. With the wind speeds of 11 and 14 m s−1 and rainfall intensities of 60 and 100 mm h−1, two levels of interaction (11 m s−1 × 60 mm h−1 and 14 m s−1 × 100 mm h−1) were designed. The particle-size composition and sediment transport flux were examined in the former wind tunnel experiments, and the runoff hydrodynamic parameters and runoff and water erosion rates were determined in the following rainfall tests. The sediment reduction effect by roots (%) was used to quantify the erosion-reducing potential of roots. The results demonstrated that in the former wind tunnel experiments, compared with the bare soils, the root-permeated soils showed a slight coarsening of surface soil and had 18.03% and 35.71% less sediment transport flux at wind speeds of 11 and 14 m s−1, respectively. In the following rainfall tests, S. psammophila roots weakened the hydrodynamic intensity of overland flow and decreased runoff and water erosion rates by 13.34%, 30.70% and 4.44%, 43.72% at rainfall intensities of 60 and 100 mm h−1, respectively. Different from the water erosion process of bare soils, which showed an increased fluctuated trend, the root-permeated soils presented a steady increase in the early stage of rainfall and then a decrease-stable trend at the mid and end of rainfall. In the wind tunnel–rainfall experiments, the sediment reduction effect by Salix psammophila roots showed 24.37% and 39.72% at levels of 11 m s−1 × 60 mm h−1 and 14 m s−1 × 100 mm h−1, respectively. This kind of study may provide more insights into understanding ecological impacts of sandy vegetation construction on the water–wind crisscrossed erosion region of the Chinese Loess Plateau and also sandy land.